PENGARUH PENGUNGKAPAN EMISI KARBON TERHADAP KINERJA KEUANGAN DENGAN JENIS INDUSTRI DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Naila Imara; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of carbon emission disclosure on corporate financial performance, with industry type and firm size as moderating variables. Carbon emission disclosure is measured using content analysis based on the carbon emission disclosure index, while corporate financial performance is measured using Return on Assets (ROA). The moderating variables in this study are industry type, measured using a dummy variable, and firm size, measured by the natural logarithm of total assets. In addition, leverage is employed as a control variable. The population of this study consists of energy sector and technology sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sampling technique used is purposive sampling, resulting in 85 companies with a total of 255 firm-year observations. The data analysis method used in this study is multiple linear regression analysis with the Moderated Regression Analysis (MRA) approach through IBM SPSS Statistics. The results indicate that carbon emission disclosure has a positive and significant effect on corporate financial performance. Industry type moderates the relationship between carbon emission disclosure and financial performance; however, the moderating effect is negative, indicating that industry type weakens the positive effect of carbon emission disclosure on corporate financial performance. Meanwhile, firm size is unable to moderate the relationship between carbon emission disclosure and corporate financial performance.